In Uncle Sam's service : women workers with the American Expeditionary Force, 1917-1919 - Zeiger, Susan, 1959- (Ithaca, NY : Cornell University Press, 2019)
"During World War I, the first American war in which women were mobilized on a mass scale by the armed services, more than sixteen thousand women served overseas with the American Expeditionary Force. Although wealthy women volunteers--members of the so-called 'heiress corps'--monopolized public attention, Susan Zeiger reveals that the majority of AEF women were wage-earners. Their motives for enlistment ranged from patriotism to economic self-interest, from a sense of adventure to a desire to challenge gender boundaries. Zeiger uses diaries, letters, questionnaires, oral histories, and memoirs to explore the women's experience of war. She draws upon insights from labor history, political history, popular culture, and the study of gender and war to analyze the ways in which women's wartime service heightened and made visible the contradictions in the prevailing gender relations. Zeiger argues that the interests of AEF women clashed with those of the wartime state at a crucial historical moment. Women sought to expand their personal opportunities for mobility and professional success and lay claim to equal citizenship. The government, determined to contain the disruption to the status quo, created a separate, subordinate status for women in the military, 'domesticating' women's service and reinscribing it within conventional limits."--Provided by publisher
Acknowledgments -- Introduction -- 1. Mobilizing Women For War -- 2. Getting Over There: A Social Analysis Of Women's Enlistment -- 3. Serving Doughnuts To The Doughboys: Auxiliary Workers In France -- 4. "The Stenographers Will Win The War": Army Office Workers And Telephone Operators -- 5. "Compassionate Sympathizers And Active Combatants": Army Nurses In France -- 6. Serving Uncle Sam: The Meaning Of Women's Wartime Service -- Notes -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 25. Sep 2019).
JSTOR
Keywords: World War, 1914-1918 -- Women -- United States; United States -- Armed Forces -- History -- World War, 1914-1918.; Guerre mondiale, 1914-1918 -- Femmes -- États-Unis.; HISTORY -- United States -- 20th century; Armed Forces; Women; United States; 1914-1918; History